2017
DOI: 10.1128/genomea.00267-17
|View full text |Cite|
|
Sign up to set email alerts
|

Draft Genome Sequence of Streptomyces scabrisporus NF3, an Endophyte Isolated from Amphipterygium adstringens

Abstract: We report the draft genome sequence of Streptomyces scabrisporus NF3, an endophyte isolated from Amphipterygium adstringens in Chiapas, Mexico. This strain produces a new modified linaridin peptide. The genome harbors at least 50 gene clusters for synthases of polyketide and nonribosomal peptides, suggesting a prospective production of various secondary metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…GMKU 363 harbor three type I PKS gene clusters associated with the synthesis of linfuranone (Komaki et al, 2015 ). Streptomyces scabrisporus NF3, an endophyte isolated from Amphipterygium adstringens , carries at least 50 gene clusters for the synthasis of polyketides and nonribosomal peptides (Vazquez-Hernandez et al, 2017 ). Genome sequence of Streptomyces sp.…”
Section: Biosynthetic Gene Clusters In Endophytic Actinobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…GMKU 363 harbor three type I PKS gene clusters associated with the synthesis of linfuranone (Komaki et al, 2015 ). Streptomyces scabrisporus NF3, an endophyte isolated from Amphipterygium adstringens , carries at least 50 gene clusters for the synthasis of polyketides and nonribosomal peptides (Vazquez-Hernandez et al, 2017 ). Genome sequence of Streptomyces sp.…”
Section: Biosynthetic Gene Clusters In Endophytic Actinobacteriamentioning
confidence: 99%
“…Similarly, Streptomyces sp. XY006, an endophyte isolated from Tea ( Camellia sinensis ) had 27 possible secondary metabolite biosynthetic gene clusters encoding for antimycin, melanin, informatipeptin, albaflavenone, and roseoflavin (Vazquez-Hernandez et al, 2017 ). Genome mining of Streptomyces wadayamensis A23, an endophytic strain showed the presence of biosynthetic gene clusteres for antimycins and candicidin (Angolini et al, 2016 ).…”
Section: Biosynthetic Gene Clusters In Endophytic Actinobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis suggested variations between KM-4927 T and DSM 41855 strains with changes in some of their polyketide biosynthetic genes [32]. Furthermore, a recent comparison made by our research group between the strains DSM 41855 and NF3, suggested important differences in their putative gene clusters encoding for secondary metabolites production [33]. Finally, the presence of 2 clades in the S. scabrisporus phylogenetic tree, with more than 60% bootstrap value, may support significant dissimilarities within this species.…”
Section: Discussionmentioning
confidence: 89%
“…The genome sequence of SS NF3 was previously reported [ 28 ]. The genome is linear and has a 71.61% of GC content ( Fig 1 ), falling into the normal range for a streptomycete and a size of 10.95 Mbp, falling in the top 5% of known Streptomyces genomes ( S1 Fig ).…”
Section: Resultsmentioning
confidence: 99%